Influence of Endophytic Bacteria on Growth and Tuber Production in Potato - Bansal, Alpi (My University, 2011)
Potato cultivar FC-3 cultures were showing the constant bacterial contamination which seems to be leaking from the internal tissues during multiplication cycles. Furthermore the cultures of cultivar FC-3 were underperforming in comparison to the other cultivars such as FC-1 and FC-4. In the present study, the effect of bacteria isolated from the the potato cultivar FC-3 was tested on the growth of potato cultivars. Bacteria from the FC-3 cultivar was isolated, characterized and inoculated into the three potato cultivars; FC-3, FC-4 and ATL. Both in vitro and ex vitro studies were carried out. The known growth promoting endophytes Pseudomonas corrugata (PC) and Bacillus subtilis (BS) were used as reference organisms to study the effect of inoculations with isolated endophytic bacteria from cultivar FC-3. FC-3 bacteria (FC-3 B) was found to be gram positive, cocci shaped, showed IAA production and it showed 98% similarity with Paenibacillus sp. In all the three cultivars, FC-3 bacteria was found to inhibit the plant growth in terms of height of plants, survival rate, weight of tubers, biomass increment as compared to plants in which no treatment was given. Whereas, P C and B S were able to show their growth promoting activity in all cultivars, but their activity was less observed in FC-3 cultivar as compared to FC-4 and ATL, due to the reason FC-3 cultivar found to inhabit FC-3 B, but P C and B S inoculated FC-3 plants showed better growth as compared to FC-3 B inoculated FC-3 plants.
M.Sc. (Biotechnology)
Keywords: Endophytic Bacteria